2014
DOI: 10.1088/0963-0252/23/2/025015
|View full text |Cite
|
Sign up to set email alerts
|

A current driven capacitively coupled chlorine discharge

Abstract: The effect of driving current, driving frequency and secondary electrons on capacitively coupled chlorine discharge is systematically investigated using a hybrid approach consisting of a particle-in-cell/Monte Carlo simulation and a volume-averaged global model. The driving current is varied from 20 to 80 A m −2 , the driving frequency is varied from 13.56 to 60 MHz and the secondary electron emission coefficient is varied from 0.0 to 0.4. Key plasma parameters including electron energy probability function, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 65 publications
(102 reference statements)
3
17
0
Order By: Relevance
“…The difference between the measured values is explained by the passivation of the plasma chamber toward Cl-atom recombination [50]. In this current study, we assume that as a Cl atom hits the electrode, it is quenched and returns as a thermal Cl atom with 50% probability or it recombines to form a thermal Cl 2 molecule with 50% probability, which is consistent with our previous studies [31][32][33]. For this current study both the electron reflection coefficient and the secondary electron emission yield at the electrodes are set to zero.…”
Section: The Simulationsupporting
confidence: 89%
See 2 more Smart Citations
“…The difference between the measured values is explained by the passivation of the plasma chamber toward Cl-atom recombination [50]. In this current study, we assume that as a Cl atom hits the electrode, it is quenched and returns as a thermal Cl atom with 50% probability or it recombines to form a thermal Cl 2 molecule with 50% probability, which is consistent with our previous studies [31][32][33]. For this current study both the electron reflection coefficient and the secondary electron emission yield at the electrodes are set to zero.…”
Section: The Simulationsupporting
confidence: 89%
“…Earlier we developed a reaction set for particle-incell/Monte Carlo (PIC/MCC) simulation of the chlorine discharge [31]. We have explored the influence of discharge pressure on a voltage driven SF capacitively coupled chlorine discharge [31] and the role of the driving current amplitude, driving frequency and secondary electron emission on a current driven SF capacitively coupled chlorine discharge [32]. Furthermore, we explored a 'classical' DF capacitively coupled chlorine discharge [32,33] and a current driven DF capacitively coupled chlorine discharge where the parameters of the HF and the LF sources were varied independently [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the absorbed power is found to be 1.88 W and the fraction of Cl atoms is 14.1%. A more thorough analysis on the DF case are given elsewhere [5]. Fig.…”
mentioning
confidence: 99%
“…Many operating parameters can influence the discharge characteristics such as the gas pressure, the applied voltage, the gap between electrodes and the driving frequency, which is an important operating parameter in capacitive glow discharges. Thus, many researchers have studied the effect of the driving frequency on the discharge characteristics (Surendra & Graves 1991;Vahedi et al 1993;Colgan, Meyyappan & Murnick 1994;Heintz & Hieftje 1995;Kitajima et al 1998;Rakhimova et al 2006;Zhu et al 2007;Liu et al 2012;Huang & Gudmundsson 2014;Wilczek et al 2015;Sharma et al 2016;Samir et al 2017;Liu, Booth & Chabert 2018;Sharma et al 2018). These studies have shown a significant change in the discharge properties with a change in the driving frequency.…”
Section: Introductionmentioning
confidence: 99%